Towards a unified theory of transitional justice - Winter, Stephen (International journal of transitional justice, 2013)
This article argues in favour of theorizing transitional justice in established democracies. Using a New Zealand example, the article employs liberal theory to develop a legitimating account of transitional justice. This account not only offers ways of replying to those who critique the transitional justice aspirations of established democracies but also constitutes a response to those who argue against the coherence of transitional justice as a theory. Although transregime legitimation is certainly not transitional justice’s only role, it is an important function and provides resources for a unified political theory of transitional justice.